Gamma-Terpinene Modulation of LPS-Stimulated Macrophages is Dependent on the PGE2/IL-10 Axis - Ramalho, Theresa R.; Filgueiras, Luciano R.; Pacheco de Oliveira, Maria Talita; Lima, Ana Luisa de Araujo; Bezerra-Santos, Claudio Roberto; Jancar, Sonia; Piuvezam, Marcia Regina (Planta Medica, 2016)
Gamma-terpinene is a monoterpene present in the essential oils of several plants, including those from the Eucalyptus genus. This molecule was recently described as anti-inflammatory and microbiocidal, but little is known about the mechanisms behind its effects. The aim of the present study was to investigate the effect of gamma-terpinene on the lipopolysaccharide-induced production of cytokines by murine peritoneal macrophages. Gamma-terpinene treatment was found to reduce the production of proinflammatory cytokines, such as interleukin-1β and interleukin-6, and enhance that of the anti-inflammatory cytokine interleukin-10. This was accompanied by increased levels of the enzyme cycloxygenase-2 and its product, the lipid mediator prostaglandin E2. Inhibition of cycloxygenase-2 with nimesulide abolished the potentiating effect of gamma-terpinene on interleukin-10 production. Moreover, nimesulide treatment also abrogated the inhibitory effect of gamma-terpinene on interleukin-1β and interleukin-6. Furthermore, in macrophages from mice deficient in the interleukin-10 gene, gamma-terpinene failed to inhibit interleukin-1β and interleukin-6 production. These results suggest that this monoterpene promotes the prostaglandin E2/interleukin-10 axis, which inhibits the production of these proinflammatory cytokines.
Keywords: gamma-terpinene; macrophage; cycloxygenase-2; prostaglandin E2